2020
DOI: 10.1111/ajt.15996
|View full text |Cite
|
Sign up to set email alerts
|

Viral shedding prolongation in a kidney transplant patient with COVID-19 pneumonia

Abstract: COVID-19 had full recovery. 5 On the other hand, immunosuppression may prolong viral shedding time. Traces of SARS-CoV-2 RNA are not necessarily correlated with transmissibility. Nevertheless, longer observation periods should be considered. Serial IgG/IgM antibody tests might be conductive to ascertaining the situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 5 publications
4
39
0
1
Order By: Relevance
“…Hydroxychloroquine sulfate and chloroquine phosphate, historically, anti-malaria drugs, have also been investigated for treatment of COVID-19 in clinical trials. 64,65 In the current study, hydroxychloroquine was used in 54.8% (121/221) of KTx patients, most frequently in those with severe symptomatology [18][19][20][21]24,27,28,[30][31][32]34,[36][37][38][39][40][41][43][44][45][46][47][48]51 , and umifenovir, alone or in combination. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41]…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 76%
See 1 more Smart Citation
“…Hydroxychloroquine sulfate and chloroquine phosphate, historically, anti-malaria drugs, have also been investigated for treatment of COVID-19 in clinical trials. 64,65 In the current study, hydroxychloroquine was used in 54.8% (121/221) of KTx patients, most frequently in those with severe symptomatology [18][19][20][21]24,27,28,[30][31][32]34,[36][37][38][39][40][41][43][44][45][46][47][48]51 , and umifenovir, alone or in combination. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41]…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 76%
“…Laboratory evaluation was included in 33 of 37 studies. 18,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44]46,[48][49][50][51][52][53][54] Most patients presented with lymphopenia appears to be self-limited and its clinical implications are not well described in the literature. 60 Regarding radiographic findings in KTx COVID-19-infected patients, 78.5% presented with bilateral ground-glass opacities in both chest plain radiograph and CT scan of the chest.…”
Section: Symptomatology and Laboratory Findingsmentioning
confidence: 99%
“…First, there is concern that organ transplant recipients may be at a greater risk for acquiring and experiencing worse clinical outcomes due to COVID-19 infection [5][6][7]. Second, immunosuppressed KT recipients may have prolonged viral shedding and transmissibility, potentially posing a greater risk to public health [8,9]. Third, there is concern that hospitals will not have the resources to safely perform KT and provide the necessary postoperative care [10].…”
Section: Introductionmentioning
confidence: 99%
“…These two patients finally transferred to ARDS (Acute respiratory distress syndrome), and eventually died after [10]. Among the immunocompromised patients, Zhang et al [11] reported a patient with kidney transplantation who had a prolonged viral shedding duration for 63 days. This is the first report of a patient co-infected with HIV and SARS-CoV-2 who showed a prolonged viral shedding duration.…”
Section: Discussionmentioning
confidence: 99%